Gaduh goats in rotation and poverty alleviation efforts: A case study in a mountain village in Indonesia - Hanif, Muhammad; Pujiati, Pujiati; Sulistyarsi, Ani (Edelweiss Applied Science and Technology, 2025)
The aim of this research is to determine the effectiveness of implementing the goat-raising model in increasing the income of the poor residents of Sodong, Indonesia. This research sought various types of information: goat-raising models, surveys, and interviews with low-income individuals. The results of the research show that the appropriate goat-raising model for increasing the income of the poor residents of Sodong Hamlet is the rotational goat-raising model. The rotational model of goat raising involves raising goats owned by the community with a profit-sharing system in the form of baby goats or money from sales profits. The increase in income is obtained from sharing the results of goat kids from parent goats (females) or sharing profits from the sales of feeder goats (males). Apart from that, the goat raisers also received additional income from selling goat dung and wages for finding feed for others.